2003
DOI: 10.1016/s0021-9517(03)00157-x
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of Cu/ZnO catalysts for the single-stage gas-phase processing of dimethyl maleate to tetrahydrofuran

Abstract: Bifunctional catalysts consisting of copper, zinc oxide, and γ -alumina have been produced by means of extrusion. The effects of formulation and forming conditions on morphology, pore texture, and copper surface area are discussed. These extruded catalysts have been employed in the fixed-bed gas-phase conversion of dimethyl maleate at temperatures between 453 and 493 K and space velocities ranging from 0.2 to 2.4 h −1 . Copper catalyzes the hydrogenation and hydrogenolysis reactions yielding γ -butyrolactone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 11 publications
(15 reference statements)
1
24
0
Order By: Relevance
“…The surface areas (S BET ) of the calcined catalysts increased monotonically from 196.4 to 261.7 m 2 ·g −1 with the increase in the content of γ-Al 2 O 3 , though they were generally lower than that of γ-Al 2 O 3 (A 0-0-01 ) ( Table 1). This is consistent with the study by Kraushaar-Czarnetzki et al [34]. …”
Section: Bet Characterizationsupporting
confidence: 94%
See 2 more Smart Citations
“…The surface areas (S BET ) of the calcined catalysts increased monotonically from 196.4 to 261.7 m 2 ·g −1 with the increase in the content of γ-Al 2 O 3 , though they were generally lower than that of γ-Al 2 O 3 (A 0-0-01 ) ( Table 1). This is consistent with the study by Kraushaar-Czarnetzki et al [34]. …”
Section: Bet Characterizationsupporting
confidence: 94%
“…The Cu-ZnO/Al 2 O 3 catalysts were prepared by means of the precipitation-extrusion method [34]. γ-Al 2 O 3 produced from boehmite (>400 mesh and 26% m/m water, Shandong Aluminum Corp., Zibo, China), Cu(NO 3 ) 2 ·3H 2 O (Sinopharm Chemical Reagent Co., Ltd., Shanghai, China), and Zn(NO 3 ) 2 ·6H 2 O (purchased from Sinopharm Chemical Reagent Co., Ltd., Shanghai, China) were dissolved in water with a final total metal concentration of 1.4 M. Aqueous Na 2 CO 3 (0.3 M) was used as a precipitating agent.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity of BDO increased linearly at the expense of GBL with increasing pressure, which suggests the presence of reversible inter-conversion between GBL and BDO. 15,18,19 At 1.0 MPa, the selectivity of THF was improved to 12.0%, and no enhancement was found at higher pressures. The above results indicate that the co-precipitated CuO-ZnO is a promising catalyst for the hydrogenolysis of DES.…”
Section: Resultsmentioning
confidence: 95%
“…17 the cyclo-dehydration of BDO to THF has been weakly catalyzed by CuO-ZnO catalyst with a low selectivity to the target THF (Scheme 1). 16 -18 Müller et al 19 reported that dimethyl succinate was completely converted to THF over CuO-ZnO/Al 2 O 3 at 220…”
Section: Introductionmentioning
confidence: 99%